(untitled) (Journal of Partial Differential Equations, 2020)
Some abstract results about convergences for a sequence of parameterized nonempty closed convex sets, in the Mosco sense as well as in the sense of the local gap have been proved. By using these results, the convergences of some sequences of closed convex sets by certain general concrete structures arc discussed.